2008
DOI: 10.1007/s00253-008-1635-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PEG-carboxylate dehydrogenase and glutathione S-transferase in PEG metabolism by Sphingopyxis macrogoltabida strain 103

Abstract: Sphingopyxis terrae and the Sphingopyxis macrogoltabida strains 103 and 203 are able to degrade polyethylene glycol (PEG). They possess the peg operon, which is responsible for the conversion of PEG to PEG-carboxylate-coenzyme A (CoA). The upstream (3.0 kb) and downstream (6.5 kb) regions of the operon in strain 103 were cloned and sequenced. The structure was well conserved between S. macrogoltabida strain 203 and S. terrae, except that two sets of transposases are absent in strain 203. The downstream region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…28) Judging from the nature of this kind of protein (located on the cytoplasmic membrane as a translocator), the enzyme might be responsible for the translocation of PEG-carboxylate from the periplasm into the cytoplasm or for the detoxification of strong acidity of the substrate. Since glutathione S-transferase (a gene coding this enzyme is located in the downstream of the peg operon) is localized in the cytoplasm and suggested to buffer the toxicity of PEG-carboxylateCoA, 29) the role of acyl-CoA synthetase might be to buffer the toxicity of PEG-carboxylate (perhaps a low molecular size) together with glutathione S-transferase. Other two genes code proteins related to transport, TonB-dependent receptor and permease respectively.…”
Section: Microbial Degradation Of Synthetic Water-soluble Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…28) Judging from the nature of this kind of protein (located on the cytoplasmic membrane as a translocator), the enzyme might be responsible for the translocation of PEG-carboxylate from the periplasm into the cytoplasm or for the detoxification of strong acidity of the substrate. Since glutathione S-transferase (a gene coding this enzyme is located in the downstream of the peg operon) is localized in the cytoplasm and suggested to buffer the toxicity of PEG-carboxylateCoA, 29) the role of acyl-CoA synthetase might be to buffer the toxicity of PEG-carboxylate (perhaps a low molecular size) together with glutathione S-transferase. Other two genes code proteins related to transport, TonB-dependent receptor and permease respectively.…”
Section: Microbial Degradation Of Synthetic Water-soluble Polymersmentioning
confidence: 99%
“…30,31) A gene coding PEG-carboxylate dehydrogenase was detected in the downstream region of the peg operon, and was found to be involved in PEG metabolism. 29) In addition, superoxide dismutase cloned from PEG-utilizing Pseudonocardia sp. strain K1 showed ether-bond-cleaving activity for carboxylated PEG.…”
Section: Microbial Degradation Of Synthetic Water-soluble Polymersmentioning
confidence: 99%
“…superoxide dismutase (RQP04715.1, RQP13424.1, RQP09887.1, RQP11889.1, RQP18047.1, RQP18034.1, RQP09190.1, RQP20377.1), as well as genes encoding enzymes involved in glutathione metabolism, which have been proposed to participate in PEG metabolism (Somyoonsap et al, 2008) were identified ( Figure 7B and Table 3).…”
Section: Glycol Ethers Degradationmentioning
confidence: 99%
“…Besides, the pathways for glyoxylate, butanoate, pyruvate and formate metabolisms as well as the TCA pathway were fully reconstructed from the BP8 metagenome ( Figure 7B). Additionally, in PEG metabolism, long chains of PEG-carboxylate can be processed by acyl-CoA synthetase and glutathione-S transferase forming glutathioneconjugates (Somyoonsap et al, 2008). Although these reactions would not be needed for glycol ethers catabolism, they could be required for the degradation of long PPG moieties that are part of the PE-PU-A copolymer ( Figure 3A).…”
Section: The Bp8 Metagenomic Analysis Allowed To Identify Known Additmentioning
confidence: 99%
“…S. terrae and Sphingopyxis macrogoltabida strains 103 and 203 can degrade polyethylene glycol (PEG), a compound utilized and released by mankind in the last 40 years. 2) They have well-conserved PEG-degradative genes coordinated as an operon, 3) containing PEG-degradative genes [4][5][6] and transcriptional regulators for the operon.…”
mentioning
confidence: 99%